Composite adaptive SMC of nonlinear base isolated buildings with actuator dynamics - Luo, Ningsu; De La Sen, Manuel; Rodellar, José (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses the problem of designing a robust active controller for nonlinear base isolated building structures in the presence of unknown seismic excitations, parametric uncertainties and actuator dynamics. A simple adaptation law is introduced to get available upper bounds for the unknown seismically excited nonlinearities.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka